Reduced item set for the amyotrophic lateral sclerosis assessment questionnaire: development and validation of the ALSAQ-5. Issue 1 (1st January 2001) - Jenkinson, C; Fitzpatrick, R
Abstract : OBJECTIVE: The 40 item amyotrophic lateral sclerosis assessment questionnaire (ALSAQ-40) is a subjective health measure designed specifically to assess areas of importance to patients with ALS. It was designed for use in surveys and clinical trials of this patient group, and has been assessed for reliability and validity. Despite its relative brevity there are situations where an even shorter form of the instrument would be desirable. Consequently, this paper reports a process of item reduction which results in a brief five item version of the instrument. METHODS: Data from two surveys of patients with ALS who completed the ALSAQ-40 were analysed to develop a short form ALSAQ. Questionnaire items were correlated with their dimension total scores. Highly correlated items were transformed onto a scale from 0 to 100 and results compared with the parent dimension. RESULTS: Five items were selected that produced results that closely resembled those of the five dimension scores of the ALSAQ-40. CONCLUSIONS: Results on the new measure compared with the parent ("gold standard") ALSAQ-40 suggest that the measure can produce similar results to the longer form but with considerable economy.